Analysis Of Sport Development Index Based On Community Participation and Physical Fitness in Cilacap Regency (Universitas Negeri Semarang, 2020)
The purpose of this study was to determine the participation index and physical fitness index of the community in terms of the Sport Development Index.The method used in this research is survey and test through a quantitative descriptive approach. The research location is in Cilacap Regency with the research objectives of North Cilacap District, Central Cilacap District and Majenang District. The data collection instruments used questionnaires and tests. The population in this study were all residents in Cilacap Regency who were over 7 years old and the sample of this study was 90 residents who were over 7 years old. Analyzed using the Sport Development Index analysis of the dimensions of participation and physical fitness of the community. The results of research in Cilacap Regency include: 1) The level of community participation in Cilacap Regency is 0.156 in the low category. 2) The level of physical fitness in Cilacap Regency is 0.311 in the low category. The conclusion of this study is that community participation in exercising in Cilacap Regency is still in the low category and the physical fitness of the community in Cilacap Regency is in the low category. The suggestion for the Cilacap Regency Government is to make a program that is useful to increase participation and physical fitness in the community.